2020
DOI: 10.3233/trd-190035
|View full text |Cite
|
Sign up to set email alerts
|

Lysinuric protein intolerance: Pearls to detect this otherwise easily missed diagnosis

Abstract: BACKGROUND: Lysinuric protein intolerance (LPI) is a rare autosomal recessive disorder characterized by deficient membrane transport of cationic amino acids. It is caused by pathogenic variants in SLC7A7, resulting in impairment of intestinal import and renal proximal tubule loss of the affected amino acids. LPI typically presents with gastrointestinal symptoms, such as vomiting, diarrhea, and failure to thrive. CASE REPORT: A 4-year-old African-American boy presented with multiple respiratory tract infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…Patients who achieve metabolic control by complying with diet and supportive treatments may experience fewer attacks. 5,6 Unfortunately, it took time to achieve metabolic control and decrease the frequency of attacks in our patients.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Patients who achieve metabolic control by complying with diet and supportive treatments may experience fewer attacks. 5,6 Unfortunately, it took time to achieve metabolic control and decrease the frequency of attacks in our patients.…”
Section: Discussionmentioning
confidence: 89%
“…4 It is inherited by pathological variants of the SLC7A7 gene located on the 14q11.2 locus of chromosome 14. 5,6 LPI been considered as a benign urea cycle disease for a long while and suggested receiving adequate treatment with an appropriate low-protein diet and L-citrulline replacement. On the contrary, in the light of our current knowledge, it is an entity with high morbidity and mortality with multi-organ involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CC-BY 4.0 International license made available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is The copyright holder for this preprint this version posted August 16, 2021. ; https://doi.org/10.1101/2021.08.15.456393 doi: bioRxiv preprint 5 mutations in Slc7a7 gene have abnormal blood count, as well as microcytic anemia (Alqarajeh et al, 2020;Rajantie et al, 1980). To date, the standard treatment for LPI mainly consists on a low-protein based diet supplemented with oral citrulline (Lukkarinen et al, 2003), where citrulline is intracellularly converted to arginine in renal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently leading to reduced body weight, brain edema and pulmonary alveolar proteinosis between other complications (Bodoy et al, 2019). In addition, several studies found that patients with one or several mutations in Slc7a7 gene have abnormal blood count, as well as microcytic anemia (Alqarajeh et al, 2020; Rajantie et al, 1980). To date, the standard treatment for LPI mainly consists on a low-protein based diet supplemented with oral citrulline (Lukkarinen et al, 2003), where citrulline is intracellularly converted to arginine in renal epithelial cells.…”
Section: Introductionmentioning
confidence: 99%